2004
DOI: 10.1039/b402993n
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of 2H-MoS2using Hay and Wadt effective core pseudo-potentials for modelling the (101̄0) surface structure

Abstract: Periodic Hartree-Fock and DFT methods were employed to calculate the geometric and electronic properties of bulk 2H-MoS 2 and of its catalytically important (101 0) edge structure. The core electrons of molybdenum and sulfur were represented by the effective core pseudo-potentials, developed by Hay and Wadt. For the calculations (101 0) type surface structures were generated by cutting sections from an 2H-MoS 2 crystal, which consists of four, six or eight rows of molybdenum and sulfur atoms. The calculated el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
(50 reference statements)
4
13
0
Order By: Relevance
“…For the hexagonal structure MoS 2 , it is reduced to five components, i.e., C 11 , C 12 , C 13 , C 33 , and C 44 . The calculated elastic constants are listed in Table 2, together with experimental [41] and previously calculated values [26,[42][43][44]. We obtain overall good agreement they seriously deviate from their nominal valence, these huge differences lie in that the Hirshfeld analysis is not a strict way in deciding the valence of an atom [39].…”
Section: Elastic Propertiesmentioning
confidence: 73%
“…For the hexagonal structure MoS 2 , it is reduced to five components, i.e., C 11 , C 12 , C 13 , C 33 , and C 44 . The calculated elastic constants are listed in Table 2, together with experimental [41] and previously calculated values [26,[42][43][44]. We obtain overall good agreement they seriously deviate from their nominal valence, these huge differences lie in that the Hirshfeld analysis is not a strict way in deciding the valence of an atom [39].…”
Section: Elastic Propertiesmentioning
confidence: 73%
“…The HF method predicts a reduction of the fundamental band gap but the surface preserves semi-conducting properties, while the DFT method predicts the first two layers to be conductive [7,24]. The present EMBED01 calculations (with correlation correction) demonstrate that the Mo and S edges remain semi-conducting, despite the fact that the HOCO-LUCO gap decreases considerably.…”
Section: The Defect and Surface Energymentioning
confidence: 57%
“…It has been shown that six to eight layers along the (1010) direction reproduce the bulk properties at the center of the slab and give an accurate description of the surface [24]. The calculations revealed that Mo surface atoms relax inwards, while the exposed sulfur atoms relax outwards and toward each other across the S-Mo-S layer.…”
Section: The Defect and Surface Energymentioning
confidence: 92%
“…Much research based on MDS has been reported on water structure and the dynamic and thermodynamic characteristics of water at mineral surfaces (Du and Miller, 2007a;Gallo et al, 2002;Kalinichev and Kirkpatrick, 2002;Lee and Rossky, 1994;Rustad, 2001;Rustad et al, 2003;Spohr et al, 1999;Wang et al, 2004). Recently, quantum chemical calculations providing electronlevel information about atomic interactions, such as Density Functional Theory (DFT), have also been used in the study of sulfide minerals, such as molybdenite (Todorova et al, 2004) and pyrite (Blanchard et al, 2007;Hung et al, 2003;Zhao et al, 2014). However, due to the magnitude of the DFT calculation, it is difficult to study the interfacial water structure using DFT when compared to MDS.…”
Section: Introductionmentioning
confidence: 99%